PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA SEKOLAH DASAR PERIODE 2020-2024 - Aentika, Ika Nisa; Yeri Sutopo; Agus Yuwono; Bambang Subali; Nuni Widiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to understand the role of pop-up books in improving elementary school students' writing skills. It employs the Systematic Literature Review Method, specifically designed to collect, assess, and analyze findings from various studies relevant to a specific research topic. The reviewed literature shows that pop-up books offer a novel solution in Indonesian language learning by presenting information interactively and engagingly through three-dimensional elements. The study's results indicate that pop-up books are effective in enhancing students' writing skills. Therefore, the use of pop-up books can be a solution for improving writing skills in elementary school students.